DNA methyltransferases in virus‐associated cancers. (3rd December 2018) - Charostad, Javad; Astani, Akram; Goudarzi, Hossein; Faghihloo, Ebrahim
Summary: Human tumor viruses are either casually linked or contribute in the development of human cancers. Viruses can stimulate oncogenesis through affecting diverse biological pathways in human cells. Growing data have demonstrated frequent involvement of one of the most characteristic parts of cellular epigenetic machinery, DNA methylation, in the oncogenesis. DNA methylation of cellular genes is catalyzed by DNA methyltransferases (DNMTs) as a key effector enzyme in this process. Dysregulation of DNMTs can cause aberrant gene methylation in promoter of cancer‐related genes including tumor suppressor genes, resulting in gene silencing. In this regard, the role of tumor viruses is remarkable. Here, in this review, we used published information to elucidate whether tumor viruses are able to manipulate DNMT regulation, and if so, what are its consequences in the process of oncogenesis. This essay also aims to shed light on which cellular pathways have been engaged by viruses to induce DNMTs.